1993
DOI: 10.1002/mus.880160512
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber conduction velocity changes with length

Abstract: While recording activity from individual muscle fibers by single fiber EMG (SFEMG), stimulated either through their axons or directly, the length of the recorded muscle fiber was changed--stretched or made shorter--by manipulating the recording needle or by passive joint movements. This resulted in significant changes of latency corresponding to an increase in propagation velocity on shortening of the muscle fiber and to a slowing of its lengthening. The maximum increase in velocity was estimated to 33% and sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 18 publications
3
22
1
Order By: Relevance
“…Myoelectric signal frequency is determined by a complex set of interacting factors. Such factors as length of muscle fibers (Doud and Walsh 1995;Trontelj 1993), type of muscle contraction, and velocity of muscle fascicle shortening (Pasquet et al 2006), fatigue (Dimitrova and Dimitrov 2003) and distance between signal source and recording electrodes (Lateva 1988) could not account for the frequency decrease after SO-LG self-reinnervation found here. The mean length of fascicles (Table 3) and the types of muscle contraction, as demonstrated by fascicle velocity plots (Fig.…”
Section: Effects Of So and Lg Self-reinnervation On Myoelectric Frequcontrasting
confidence: 41%
See 1 more Smart Citation
“…Myoelectric signal frequency is determined by a complex set of interacting factors. Such factors as length of muscle fibers (Doud and Walsh 1995;Trontelj 1993), type of muscle contraction, and velocity of muscle fascicle shortening (Pasquet et al 2006), fatigue (Dimitrova and Dimitrov 2003) and distance between signal source and recording electrodes (Lateva 1988) could not account for the frequency decrease after SO-LG self-reinnervation found here. The mean length of fascicles (Table 3) and the types of muscle contraction, as demonstrated by fascicle velocity plots (Fig.…”
Section: Effects Of So and Lg Self-reinnervation On Myoelectric Frequcontrasting
confidence: 41%
“…Muscle-tendon unit (MTU) and muscle fascicle length are measures of the kinematics of ankle extensors. The latter measure with its time derivative is also related to the muscle spindle strain and the type of muscle action (eccentric, concentric, isometric) and can influence myoelectric intensity and frequency (Doud and Walsh 1995;Pasquet et al 2006;Trontelj 1993); see DISCUSSION. In addition, elongation of ankle extensors during the joint yield in the stance phase of walking has been used as an indicator of functional recovery after muscle nerve injury (Abelew et al 2000;Maas et al 2007Maas et al , 2010. MTU length was obtained from recorded joint positions and a geometric model of the cat hindlimb (Goslow et al 1973;Gregor et al 2006;Whiting et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Kupa et al, 1995;Wakeling and Syme, 2002). Although other factors can affect the frequency content of myoelectric signals and conduction velocity -muscle length (Trontelj, 1993;Doud and Walsh, 1995), type of muscle action (eccentric or concentric) (Pasquet et al, 2006), fatigue (Dimitrova and Dimitrov, 2003) and distance between the signal source and recording electrodes (Lateva, 1988) -these factors are not expected to substantially influence the results of this study or can be accounted for. First, the mean muscle-tendon unit (Gregor et al, 2006) and muscle fascicle lengths ) of cat SO and MG do not differ greatly between level and slope walking.…”
Section: Wavelet and Principal Components Analysis Of Intramuscular Mmentioning
confidence: 85%
“…Longer fascicle length values of ankle extensors in early stance of upslope walking than in late stance ) could also contribute to lower frequency content during rising activity of these muscles (e.g. Trontelj, 1993;Doud and Walsh, 1995).…”
Section: Muscle Fibre Distribution In Ankle Extensors and Patterns Ofmentioning
confidence: 99%
“…This has been explained in terms of changes in the geometrical configuration of the muscle fibers with respect to the belly e l e~t r o d e~~,~' and in terms of supposed changes in muscle conduction velocity resulting from changes in muscle length.3y However, geometrical changes experienced by the belly electrode cannot account for the changes we observed in the beyond-the-muscle CMAPs, which did not involve the belly electrode. Moreover, experimental studhave found that there is in fact no appreies33, 43 ciable change in muscle conduction velocity when muscle fibers are compressed or stretched between ' 70 and 130% of their normal lengths.…”
Section: Multielectrodementioning
confidence: 99%